Two Channel Single Transmission Medium Laser Communication (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Light is  one of the verbalexchanges that can have aninstructionto words optical facts just like a cord emitting current. It may appear impractical way to apply lasers without a managing medium to transmit data. But it appears impractical to apply laser without a conducting medium to emitting data. Laser verbal exchange is an optical wi-fi verbal exchange estimated to be the subsequent technology wi-fi verbal exchange generation because of inherent traits like extended bandwidth, excessive facts rate, protection and immunity. It is a higher opportunity to traditional verbal exchange schemes because of its capacity features. Therefore, not like RF verbal exchange, layout and trying out the laser verbal exchange gadget is complicated tasks, because it desires to don't forget many elements associated with the conditions.The essential reason of this journey acknowledgessending and receiving instrument to change sound through withouta managing medium the usage of depth modulation with much less quality.Here the line-of-sight conditions plays very important role in transmission and reception of data.They have advantage of doing away with the desires of broadcast cables. This necessity the want of modelling to perform channel unmarried transmission medium laser verbal exchange a good way to examine and optimize the layout.